ANALISIS STRUKTUR MODAL DALAM MENINGKATKAN LABA PADA PT. LOTTE CEMICAL TITAN, TBK - Nurmiati, Nurmiati; Pratiwi, Aliah (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the capital structure used by PT. Lotte Cemical Titan, Tbk in increasing profits. This type of research is descriptive by using research instruments in the form of a list of tables containing data on total debt, total assets, total equity and net profit after tax at PT. Lotte Cemical Titan, Tbk. The population used in this study were all financial statements of PT. Lotte Cemical Titan, Tbk since being listed on the IDX from 1988 to 2020, for 32 years. The sample in this study is the financial statements of PT. Lotte Cemical Titan, Tbk for 10 years, from 2011 to 2020 using purposive sampling. Data collection techniques using documentation and literature study. The data analysis technique uses data analysis by component ratios used to measure capital structure, namely Debt To Asset Ratio (DAR) and Debt To Equity Ratio (DER), as well as ratios to measure profit, namely Return On Assets (ROA) and Return On Equity (ROE), in this study also used one-party t-test data analysis (One Sample t-test). The result of this research is PT. Lotte Cemical Titan, Tbk is not good at managing the company's capital structure in increasing profits.